Microbiological survey of birds of prey pellets. (August 2015) - Dipineto, Ludovico; Bossa, Luigi Maria De Luca; Pace, Antonino; Russo, Tamara Pasqualina; Gargiulo, Antonio; Ciccarelli, Francesca; Raia, Pasquale; Caputo, Vincenzo; Fioretti, Alessandro
Abstract: A microbiological survey of 73 pellets collected from different birds of prey species housed at the Wildlife Rescue and Rehabilitation Center of Napoli (southern Italy) was performed. Pellets were analyzed by culture and biochemical methods as well as by serotyping and polymerase chain reaction. We isolated a wide range of bacteria some of them also pathogens for humans (i.e. Salmonella enterica serotype Typhimurium, Campylobacter coli, Escherichia coli O serogroups). This study highlights the potential role of birds of prey as asymptomatic carriers of pathogenic bacteria which could be disseminated in the environment not only through the birds of prey feces but also through their pellets.